Pengaruh Literasi Keuangan, Digitalisasi Sistem Keuangan, Akses Pembiayaan, dan Manajemen Arus Kas terhadap Kinerja Keuangan UMKM di Kota Batam - Intan Juniarti; Juni Aziwantoro; Andres Putranta Sitepu; Salihi Salihi; Teddy Ramadhan (Manajerial dan Bisnis Tanjungpinang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic development, including in Batam City; however, they continue to face various challenges in financial management that affect business financial performance. This study aims to analyze the effects of accounting literacy, the implementation of digital accounting systems, access to financing, and cash flow management on the financial performance of MSMEs in Batam City. The study adopts a quantitative approach using a survey method of 100 MSMEs selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression. The results show that, both partially and simultaneously, accounting literacy, the implementation of digital accounting systems, access to financing, and cash flow management have a positive and significant effect on MSME financial performance, with the implementation of digital accounting systems being the most dominant variable. The coefficient of determination (R²) of 0.842 indicates that 84.2% of the variation in MSME financial performance can be explained by the research model. Thus, it can be concluded that improvements in MSME financial performance are strongly influenced by the integration of sound financial management, the utilization of digital technology, and support for business sustainability.